Halftone images compression of bitplane using run length encoding with confirmation of repeateation - H. K. Al-Bahadily; V. Yu. Tsviatkou; V. K. Kanapelka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Some algorithms of probabilistic coding of bits series lengths based on the confirmation of bit repetition and differing with an explicit or implicit indication of the length of the repetition symbol are proposed. The efficiency of these algorithms using for lossless compression of bit planes of halftone images is investigated.